Implementasi Modal Sosial Dan Tata Kelola Desa Wisata Terhadap Peningkatan Pendapatan Masyarakat Kabupaten Garut - Hanifah, Hani Siti; Anggraeni, Windi Ariesti; Nurbudiwati; Purnawan, Rd Ade (LPPM POLITEKNIK LP3I BANDUNG, 2024)
Tourism is believed to be an economic activity that drives the regional economy in an effort to improve community welfare through sustainable tourism development with natural and human aspects over a long period of time through a sustainable tourism agenda with elements of building, managing related to the environment, economy, social, nature and culture. The concept of tourism refers to community empowerment (community-based tourism) with the community acting as the determinant of development (Tamrin et al., 2021), including through Desa Wisata. The local wisdom Tourism Village program is part of sustainable tourism development with a rural concept with aspects of customs, socio-culture, traditional architecture, daily life, and integrated village spatial structure supported by social capital to encourage the formation of social relations and become energy for the implementation of social networks for marketing. The urgency of this research is to develop social capital in the community as the driving force for various social actions and cooperation networks as the glue that glues a community together in social rules, culture, belonging and mutual support, to achieve goals that are still low in the community. Meanwhile, the governance of the Tourism Village is still not optimal, because it does not know the proper management of tourism potential that can increase local community income. The purpose of the study was to determine the implementation of social capital and tourism village governance to increase community income in Garut Regency 2024. This quantitative research uses primary data obtained from respondents spread across 5 Tourism Villages in Garut Regency with multiple linear regression analysis techniques through SPSS software. This research is expected to be an input for regional policies and stakeholders in Garut Regency.